"Macro and Micro Factors Affecting Hedge Funds in India and Their Investment Strategies” - Jagabandhu Padhy, Amit Bathia, Kushagra Goel, Dhara Vora, Raj Shah, Ananya Bajoria (Journal of Informatics Education and Research, 2024)
This paper evaluates the performance of the Indian hedge fund database for the period of 2009- 2021 by taking a hedge fund (Eureka India Hedge Fund) to understand in-depth practical analysis. Comprehending the investing techniques utilized by hedge funds is crucial for regulators, scholars, and investors in the ever-changing financial markets. This research explores the world of Indian hedge funds intending to reveal the tactics they employ using a thorough regression analysis of the variables affecting investment returns, this study clarifies the effectiveness and distinctiveness of various approaches in the Indian financial landscape. There is a paucity of literature that particularly addresses the hedge fund environment in India because previous studies on hedge funds have primarily concentrated on developed economies. Research examining hedge fund tactics across borders offers insightful information about the larger framework of investing methods. Typical approaches have different risk-return profiles, such as macroeconomic, statistical arbitrage, event-driven, long-short equities, and macro. Despite this expansion, little is known about the precise investing strategies used by Indian hedge funds and the factors that influence their performance. Regression analysis is used in this work to try and close this gap by deciphering the complex methods that Indian hedge funds deploy and to analyse the macro and micro factors affecting hedge fund returns.